Strength estimation model for high-strength concrete incorporating metakaolin and silica fume - Razak, H.A.; Wong, H.S. (2005)
A mathematical model is presented for estimating compressive strength of high-strength concrete incorporating pozzolanic materials, based on the strength of a control ordinary Portland cement (OPC) concrete made with similar mixture characteristics and curing history. In this study, metakaolin (MK) and silica fume (SF) were used as cement replacement materials at 5, 10, and 15 by mass. Water/cementitious materials (w/cm) ratios varied from 0.27 to 0.33, and strength testing was conducted up to an age of 180 days. It was found that the strength of a pozzolanic mixture could be related to the strength of its equivalent control by a linear function. Key parameters involved in the model are the pozzolanic and dilution factors, which can be correlated to the pozzolan content in the mixture. The study concludes that the accuracy of the model increases with concrete age. At ages 28 days and above, 97 of the estimated strengths are within Â±5 of the actual value.